2011
DOI: 10.1152/ajprenal.00145.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of anemia with allogenic RBC transfusion prevents post-cardiopulmonary bypass acute kidney injury in swine

Abstract: Anemia during cardiopulmonary bypass (CPB) is strongly associated with acute kidney injury in clinical studies; however, reversal of anemia with red blood cell (RBC) transfusions is associated with further renal injury. To understand this paradox, we evaluated the effects of reversal of anemia during CPB with allogenic RBC transfusion in a novel large-animal model of post-cardiac surgery acute kidney injury with significant homology to that observed in cardiac surgery patients. Adult pigs undergoing general an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 34 publications
6
59
0
1
Order By: Relevance
“…Biochemical changes in the supernatant, plasma hemoglobin using spectromorphometry, and erythrocyte adenosine triphosphate concentrations using high-performance liquid chromatography, were assessed at weekly intervals, as previously described. 13,15 The hemolysis index was defined as plasma (hemoglobin × hematocrit)/donor unit hemoglobin. Scanning electron microscopy was performed of stored porcine erythrocytes at days 0, 14, and 42 of storage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biochemical changes in the supernatant, plasma hemoglobin using spectromorphometry, and erythrocyte adenosine triphosphate concentrations using high-performance liquid chromatography, were assessed at weekly intervals, as previously described. 13,15 The hemolysis index was defined as plasma (hemoglobin × hematocrit)/donor unit hemoglobin. Scanning electron microscopy was performed of stored porcine erythrocytes at days 0, 14, and 42 of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Blots were quantified by densitometry normalized to β-Actin (SantaCruz Biotechnology), as previously described. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Experimental studies have shown that these changes cause inflammatory organ injury through complex mechanisms including platelet and monocyte activation, endothelial injury and oxidative stress and the loss of microcirculatory autoregulation. [255][256][257][258] This results in paradoxical tissue hypoxia, despite apparently adequate oxygen delivery, tissue inflammation and organ dysfunction. The most important change that occurs in stored red cells over time is the depletion of high-energy phosphates.…”
Section: Introductionmentioning
confidence: 99%